DESCRIPTIVE STUDY OF GRAMMAR LEARNING APPLIED BY STUDENTS OF ENGLISH DIPLOMA III STUDY PROGRAM ON THEIR PERSONALITY TYPES - Deninda Dwi Putri; Mulyadi .; Indah Damayanti (Journal of English Education and Teaching, 2017)
This study attempted to find out (1) the most dominant personality of students at English Diploma III Study Program, (2) the most dominant grammar learning strategies applied by Sanguine, Choleric, Melancholic and Phlegmatic students at English Diploma III Study Program. Descriptive quantitative design was used in the study. In this study, the researcher used two questionnaires as the instrument. The instrument in the research was questionnaire. The first questionnaire adapted from Yusup (2013) to identify the students personality. The second one, the researcher used SILL version 7.0 adapted from Bayou’s research (2015) to know the use of grammar learning strategies at English Diploma III students.The result of present study shown that the most dominant personality was phlegmatic types. Then finding also  indicate that, Sanguine students preferred to use the social strategy. Followed by the Choleric students preferred to use the memory strategy. The Melancholic students  as well as the Phlegmatic students, these two types preferred to use the metacognitive strategy as their strategy when they learnt Grammar.